Identifying the Related Mode of Working and Performance of Support Teams in Cyberjaya Telecommunication Companies - Aseh, Khairi; Kenny, Kamal; Pathmanathan, Ravindran (Archives of Business Research, 2020)
While previous studies tried to study the link between the mode of working (virtual versus face-to-face) and team success; less attention were given to address this topic in telecommunications companies with complex technical support tasks. This study aims to identify the relationship between mode of working and team success in telecommunications companies. This study also aims to clarify whether the team size has a significant impact on the relationship between working mode with the team success. One hundred and twenty Cyberjaya based support professionals have completed web-based surveys, offering data on support operations in virtual and face-to-face settings, and the team success in all settings. The results showed a correlation between working mode and three factors of support team success (rpb = 0,358 and 0,248; 0,395, respectively for achievement objectives, customer satisfaction and team health. In addition, the impact of team sizes on the relationships between working mode and the three factors of team success was investigated. The data analysis did not support a significant team size impact on the relationships between the mode of working and three support team success measures.